Aproveitamento de lodo de curtume e uso de água residuária de esgoto doméstico na cultura do milho (Zea mays L.) - Pinto, Guilherme Malafaia (2015)
In this study, we carried out several experiments under protected environmental conditions, which, as a whole, aimed at the assessment of tannery sludge reuse in corn culture (Zea mays L.). In the first study (cultivar BG 7049H), chemical changes and corn yield in Haplic Plinthosol were assessed. The soil received 9 and 18 Mg.ha-1 of tannery sludge (in natura) and was irrigated with domestic wastewater. Such treatments helped increase pH values and total P, K, Mg and Ca concentrations in relation to initial values, thus improving soil fertility. However, the application of these doses, even if together with wastewater irrigation, did not provide a corn yield equivalent to that obtained with mineral fertilization. The second study involved vermicomposting of different tannery sludge doses with cattle dung. The potentiality of such treatment method in agriculture was assessed. The results showed that vermicomposts produced using Eisenia foetida presented different nutrient concentrations, favoring their use as soil conditioners. On the other hand, despite C/N ratios decreased in all treatments, indicating the maturation of the final substrate, the values observed exceeded the maximum limit established by MAPA’s Normative Instruction # 025/2009 for compound organic fertilizers, fact that led to the development of the third study of this Ph.D. thesis. The objective of this study was to detail the investigations on vermicomposting of tanning residues, using two different types of tannery sludge (liming and primary), which were also mixed with cattle dung. At the end of the experiments, vermicomposts yielded high N, P and K total concentrations, as well as pH values and C/N ratios, and N and TOC concentrations that comply with the minimum limits established by MAPA. Besides, Cu, Zn and Cr concentrations in the produced vermicomposts did not exceed the limits established by Conama’s re solution 375/2006. A fourth study followed, aiming at the analysis of a corn culture (cultivar LG 6036) in a typical Dystrophic Red Latosol (Oxisol), irrigated with domestic wastewater and adding tannery sludge vermicomposts produced in the previous study. Although the treatments promoted satisfactory soil conditions for the development and yield of corn, little or no increase in pH, EC, TOC, base saturation, OM, N, K, Cu and Fe concentrations were observed, when compared to concentrations initially identified in the soil. On the other hand, an increase in P, Ca, Mg, Mn and Zn concentrations was observed especially in the treatments that included irrigation with domestic wastewater and/or addition of tannery sludge vermicomposts. Thus, it is concluded that, contrarily to tannery sludge concentrations used in natura, tannery sludge vermicomposts plus irrigation with domestic wastewater constitute important nutrient sources for corn culture. However, we call attention to the use of these residues aiming at the possibility of increasing certain nutrients in soils, once no significant increase was observed for all elements assessed in the culture soils.